Customer Satisfaction Analysis in Hotels Using Power BI - Praba. R; Nisha. T; Yazhini. S; Keerthana M. S (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
In the hospitality industry, customer satisfaction analysis is critical, especially in hotels where the visitor experience has a significant impact on company results. Using Power BI, this study explores the cleverness of customer happiness in hotels, highlighting critical indicators and insights from guest feedback data. By using skillful data visualization, trend analysis, and sentiment analysis, the study aims to provide hotel management with useful information to increase visitor happiness and raise service standards. It revolves around the adept use of Power BI, a robust business intelligence tool, to create an interactive dashboard for visualizing customer feedback in the field of hotel management. This dataset enclose a various range of feedback collected from surveys and reviews. Through the development of this dashboard, the project aims to provide hotel managers with an user-friendly tool to gain comprehensive insights into customer sentiment. Also, the project compares how well the hotel is doing compared to other similar places. This helps understand how effective the hotel is in its operations. The insights from these visuals give practical recommendations, empowering hotel managers and stakeholders to make smart decisions based on data. This Data Visualization lead to Performance analysis in order yield better results.